Preparation and Characterization of Ginger Peel Polysaccharide-Zn (II) Complexes and Evaluation of Anti-Inflammatory Activity - Wenwen Li; Zhichang Qiu; Yue Ma; Bin Zhang; Lingyu Li; Qiulin Li; Qiuxia He; Zhenjia Zheng (MDPI AG, 2022)
The present study aimed to explore the improvement of the bioactivity of ginger peel polysaccharides (GPs) by the modification of zinc after structural characterization. The obtained GP-Zn (II) complexes consisted dominantly of glucose and galactose in a mass proportion of 95.10:2.10, with a molecular weight of 4.90 × 105 Da and a Zn content of 21.17 mg/g. The chelation of GPs and Zn (II) was mainly involved in the O-H of hydroxyl groups, and this interaction reduced the crystallinity and decreased the asymmetry of GPs, with a slight effect on the thermal stability. The administration of GPs and their Zn (II) complexes effectively alleviated CuSO4-induced inflammatory response in zebrafish (Tg: zlyz-EGFP) via down-regulating the mRNA expression levels of pro-inflammatory cytokines (IL-1β, IL-6, IL-8, IL-12 and TNF-α) and upregulating the expression of anti-inflammatory cytokine (IL-10). Furthermore, the modification of Zn (II) enhanced the inflammation-inhibiting effect of polysaccharides. Therefore, GP-Zn (II) complexes could be applied as a candidate anti-inflammatory agent for the treatment of chronic inflammation-related diseases.